The Role of Workplace Ostracism on Turnover Intention through Job Stress and Perceived Organizational Support among Gen Z employees - Zamralita Zamralita; Khalidatul Rafi’ah (Journal of Educational, Health and Community Psychology, 2026)
This study examined the effect of workplace ostracism on turnover intention among Generation Z employees, with job stress as a mediating variable and perceived organizational support as a moderating variable. Using a quantitative, non-experimental design, data were collected from 192 employees via self-administered questionnaires and analyzed using variance-based structural equation modeling. The results showed that workplace ostracism had a significant positive effect on job stress (β = 0.493, p < 0.001) and turnover intention (β = 0.513, p < 0.001). Job stress partially mediated the association between workplace ostracism and turnover intention (indirect effect β = 0.083, p = 0.018). Perceived organizational support was negatively associated with turnover intention (β = −0.201, p = 0.004); however, it did not moderate the relationship between workplace ostracism and turnover intention (WO × POS → TI: p = 0.507). Overall, the findings suggest that interpersonal exclusion operates as a salient stressor for Generation Z employees, increasing turnover intention partly through heightened job stress, while perceived organizational support exerts a direct protective effect but does not buffer the adverse impact of ostracism.